Banca extranjera y cambios en la estructura del crédito bancario en el Perú: 2001-2008 - Cortez Cortez, Gaby (2009)
The entry of foreign banks in Peru, has not only helped to stimulate domestic banks through greater competition, but to improved efficiency, cost management, and a variety of financial products and services that are offered. The paper analyzes the changes in the structure of direct loans from the banking system in Peru, as a result of the participation of banks of foreign origin, which conducts an assessment of the components of direct credit, such as commercial, consumer, microenterprise, and mortgage loans.